Penatalaksanaan Fisioterapi pada Kasus Post Operasi Meniscus Repair Dextra di Klinik Karya Kasih - Muliati, Muliati; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Irwansyah, Ilham (Jurnal Riset Hesti Medan, 2023)
Meniscus tear is one of the most common knee injuries treated. The meniscus is essential for normal knee function, including load transmission, joint stability, lubrication, and nutrition of the articular cartilage. Loss of normal meniscus function leads to increased knee contact pressure and articular cartilage degeneration over time. Meniscus repair (meniscus repair) is one type of surgery performed. When the meniscus has to be operated on by sewing the torn meniscus. Physiotherapy plays an important role in meniscus repair with isometric, isokinetic exercises that aim to strengthen the grub of weak muscles. Objektive: improve to the next phase and increase functional activity to be able to return to the sports field. Methods: subjects were given isometric and isokinetic strengthening exercises for 4 weeks which were performed 3x/week. Results: evaluation was carried out using Visual Analog Scale (VAS), Range Of Motion (ROM) measurement instruments, Manual Muscle Testing, and Anthropometry. Conclusion: there was an increase in ROM, MMT, and Anthropometry after being given therapy exercise for 4 weeks.